Peran Keluarga Terhadap Pemenuhan Gizi Anak Usia Sekolah - Munifa Munifa; Juni Ramadhani; Aldian Yusup (POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA, 2022)
Abstract – School age is a productive age in the process of child development. Adequate nutrition is needed by children in the process of growth and development. Fulfillment of good nutrition will also have an impact on good health in children. In meeting nutritional needs, the family has an important role in determining children's nutritional behavior. Objective: to analyze the role of the family in fulfilling child nutrition. Methods: using descriptive quantitative research methods, using a cross section study research design with data collection techniques carried out using a random survey of 30 elementary school children. The method of data analysis was used to determine the relationship between the type of mother's work and the level of education with the fulfillment of child nutrition using descriptive analysis using the Chi square test (x2). Research Results: Mother's type of work has no significant effect on children's breakfast habits with a value of ρ-value = 0.369, but has a significant effect on the habit of carrying lunch with a value of ρ-value = 0.029. Meanwhile, mother's level of education has a significant relationship with breakfast habits with ρ-value = 0.024 and bringing lunch to school with ρ-value = 0.000081.